Low pressure reverse osmosis membrane for rejection of heavy metals - Hamdzah, Myzairah (2007)
Low Pressure Reverse Osmosis Membrane (LPROM) has been introduced to water and wastewater industries in the past few years due to the high cost of operational and maintenance of conventional high-pressure RO membrane system. LPROM may remove more than 90% of heavy metals depending on the operating conditions of the system. LPROM with operating pressure less than 100 psi is commercially available to make treatment system more affordable and cost effective. Therefore, the aim of this study was to produce high-quality drinking water using LPROM system by removing heavy metals and other contaminants. The main objective of this study was to evaluate the effectiveness of LPROM for rejection of heavy metals, under different operating parameters (i.e. pressure, feed concentrations and pH). A commercially available LPROM (ES20) system manufactured by Nitto Denko Company was used in this study. The experimental design was carried out using Response Surface Methodology (RSM). Two types of wastewater containing heavy metals (i.e. synthetic polluted water containing copper and magnesium from copper chloride and magnesium sulphate solutions, and raw water from exmining pool from Tasik Biru, Sarawak) were studied. The experimental study for copper showed that higher operating pressure increased permeate flux and higher feed concentration and pH values increased the percentage of removal. However, the two-way interaction parameter (i.e. pressure vs. pH, pressure vs. feed concentration and pH vs. feed concentration) showed insignificant effects in determining permeate flux and copper removal. For magnesium, all parameters and all two-way interaction were significant in determining the percentage of magnesium removal. The higher the operating pressure resulted in a higher permeate flux and percentage of magnesium removal. A higher the value of pH has caused a lower permeate flux. However, it will increase the percentage of magnesium removal. Besides, the higher the feed concentration of magnesium was also resulted the higher percentage of magnesium removal. The optimum range of operating pressure for both copper and magnesium removal was between 90 to 120 psi and at pH between 5.5 and 7.5. The optimum statistical model for these processes based on the experimental conditions of this study indicates that operating pressure was the most significant parameter in determining the permeate flux. However, the statistical analysis of heavy metals removal was statistically insignificant and showed that the range of parameters in the study appears to be less significant to develop a sensitive and comprehensive model. This was due to the transport or separation mechanism between micropollutants and membrane surface, effect of chemical characteristics as well as effect of metal complexation. As a conclusion, operating conditions such as operating pressure and pH must be taken into account when designing the LPROM system for an optimum process in order to achieve a better heavy metals removal with higher permeate flux.